2016
DOI: 10.12955/cbup.v4.817
|View full text |Cite
|
Sign up to set email alerts
|

Teacher’s Attitude Towards the Inclusion of Students With Disabilities in Regular Schools

Abstract: Abstract:The inclusion of children with disabilities in general schools depends on teachers and pupils. The aim of this study is to evaluate the teachers' role in the inclusion of children with disabilities in general schools. Taking their role into consideration, we will be able to understand factors that influence the positive or negative attitude towards the inclusion of children with disabilities in general classrooms. 146 teachers participated in this study. The instrument used (created by Jeffrey Bailey)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…However, it is better to communicate directly with the inclusive student's parents. It is in line with Lika (2016) and Hassan et al (2015) explanation who stated that parents' interaction is very necessary. The parents must meet the teachers and discuss the problems of their children because it gives many benefits.…”
Section: Classroom Climatesupporting
confidence: 87%
See 2 more Smart Citations
“…However, it is better to communicate directly with the inclusive student's parents. It is in line with Lika (2016) and Hassan et al (2015) explanation who stated that parents' interaction is very necessary. The parents must meet the teachers and discuss the problems of their children because it gives many benefits.…”
Section: Classroom Climatesupporting
confidence: 87%
“…Discussion between the teacher and parents will improve the students' academic and social development. Although the teacher answered in the interview that it was not hard to deal with the slow learner with physical disability student because he was calm in the class, it is better to discuss directly with the parents to support the learning process as it is suggested by Lika (2016) and Hassan et al (2015).…”
Section: Classroom Climatementioning
confidence: 99%
See 1 more Smart Citation
“…Most research on the influence of gender on teachers' attitudes about the inclusion of children with developmental disabilities shows that female teachers exhibit more positive one (Al-Zyoudi, 2006;Avramidis & Norwick, 2002;Gallego-Ortega & Rodriguez-Fuentes, 2021;Koliqi & Zabeli, 2021;Mahajan, 2015;Mouchritsa et al, 2022;Parasuram, 2006;Shari & Vranda, 2016). However, there are also studies where no differences were found (Aldosari, 2022;Đorđević et al, 2018;Lika, 2016;Ozer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have shown what affects the teacher attitude towards inclusive education, Lika conducted a quantitative study to six schools in the city of Tirana in Albania (Lika, 2016). Here, the researcher took only two considerations which are the gender and their teacher training.…”
Section: Teachers' Attitude Towards Inclusive Educationmentioning
confidence: 99%